Analysis of the Influence of Transformational Leadership, Competence, and Motivation on Performance Management Effectiveness at the National Nutrition Agency - Maharani Diyan Ayu; Veithzal Rivai Zainal; Azis Hakim (Dinasti Publisher, 2025)
This study explores the influence of transformational leadership, employee competence, and work motivation on the effectiveness of performance management at the National Nutrition Agency (BGN). As a new government agency that executes national priority programs in the field of nutrition, BGN faces challenges in terms of organization, human resource capacity, and accountability systems. The study uses an explanatory quantitative approach with a sample of 50 employees (proportional random sampling). Primary data were collected through a 1–5 Likert-scale questionnaire that had been tested for validity and reliability; secondary data were obtained from BGN performance reports. The analysis included classical assumption testing and multiple linear regression (SPSS). The results show that transformational leadership has a positive and significant effect on the effectiveness of performance management (β = 0.352; p < 0.01), motivation has a positive and significant effect (β = 0.298; p < 0.05), while competence has a positive but insignificant effect (β = 0.121; p > 0.05). Simultaneously, the three variables explain 61.3% of the variation in effectiveness (R² = 0.613). The findings indicate that strengthening leadership and motivation systems should be prioritized by BGN, while competency development strategies should be adjusted to have an impact on performance outcomes. This study recommends the development of leadership development programs, competency-based training, and a clearer reward system to strengthen BGN's performance management.